Family and gender : changing values in Germany and India - Ahmad, Imtiaz; Pernau, Margrit; Reifeld, Helmut (Sage Publications, 2003)
This Indian book brings together, for the first time, essays written by well-known scolars from a wide range of academic disciplines in the various aspects of family in India and Europe, with special reference to Germany.